PP35 How are Health Inequalities Affected by Control in the Living Environment? A Critical Review of Theory. (10th September 2013) - Orton, L C; Pennington, A J; Nayak, S; Petticrew, M; White, M; Sowden, A; Whitehead, M
Abstract : Background: Recent public health strategies aim to increase the control, or power, that individuals, communities and populations have over decisions that affect their daily lives. While systematic reviews have revealed the health impact of measures to improve control in the work environment, evidence from the 'living environment' has not been synthesised. We conducted a critical review of proposed theories and causal pathways linking control in the living environment and socio-economic inequalities in health. Methods: We identified theoretical discourses (published in books, academic papers, reports and policy documents) across a range of diverse fields, including: public health, social determinants of health and health inequalities; sociology/political science; and international development. Initially, seminal works were identified by experts. We then employed a 'pearl-growing' approach: hand-searching reference lists and asking key informants to identify additional publications. Theoretical elements were extracted and analytical frameworks developed to elucidate the pathways identified. Results: On reviewing a substantial body of literature, we found the relationship between control in the living environment and health inequalities had been conceptualised at three levels: Personal level Low perceived control impacts on health via fatalism and hostility reactions, which are engendered by social position and the cumulative effects of chronic stress across the lifecourse. Micro/Meso level The immediate external environment, determined by social position, dictates opportunities for individuals and communities to exercise autonomy and control over their living conditions. This effect occurs at the individual, household and community levels, and is important for health via control beliefs (as above), people's abilities to improve their living conditions and avoid disease risks, and through community trust and reciprocity. Macro level Socio-political structures and processes operate at the level of whole societies, stratifying access to resources and opportunities, or power, that people have to achieve good health. This can result in better health outcomes for low-income populations with greater gender equity; and negative outcomes for whole societies in which people lose the opportunity for control over their lives. Conclusion: Theories proposed on how control in the living environment could lead to the generation of socio-economic inequalities in mental and physical health reveal a range of processes at individual, micro/meso and macro levels. The findings of this critical review are being used to inform a theory-led systematic review of empirical evidence examining the links between control and health. This will allow us to refine the conceptual pathways, and identify potential intervention points and promising interventions.